Dual effects of indoxyl sulfate on modulation of human hepatic CYP3A activity, with individual differences. - Masao Togao; Naoyuki Asakawa; Gaku Wagai; Yuki Ohta-Takada; Jun Otsuka; Minoru Ando; Akinobu Kurita; Koji Kawakami (PLoS ONE, 2025)
This study aimed to identify gut microbiota-derived metabolites governing the activity of hepatic CYP3A in blood level. Indole propionic acid (IPA) and lithocholic acid, ligands of the pregnane X receptor, a transcriptional regulator of CYP3A, and various gut microbiota-derived metabolites in blood level were analyzed. Results revealed that IPA and lithocholic acid did not affect CYP3A activity, while indoxyl sulfate (IS), a uremic toxin, affected CYP3A across different cell lines. The effects of IS on primary hepatocytes from three donors were analyzed, and a concentration-dependent impact was observed, as the CYP3A activity decreased in one donor and increased in another. These findings offer initial insights into blood-level gut microbiota-derived metabolites influencing hepatic CYP3A. Furthermore, the study demonstrates that the response to IS, beyond its concentration, can cause variations in hepatic CYP3A activity among individuals. This study advocates accounting for the dual effects of IS and the benefits of personalized medicine.